COURSE OF ANEMIA IN DIFFUSE TOXIC GOITER (Global Conference on Medical and Health Sciences, 2026)
This article describes the causes, clinical course, and specific features of anemia in patients with diffuse toxic goiter (thyrotoxicosis). It analyzes the effects of thyroid hormone overproduction on accelerated metabolism, impaired absorption of iron and vitamin B12, and the role of autoimmune factors in the development of anemia. The importance of timely diagnosis and correction of anemia alongside the treatment of thyrotoxicosis to improve patients' quality of life is emphasized.
Keywords: Diffuse toxic goiter, thyrotoxicosis, anemia, thyroid gland, metabolism, iron deficiency.